(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2020)
This article has no abstract. The first 100 words appear below: A 28-year-old woman came with severe pain on the lower left quadrant of the mouth. She already had an orthopantomogram (panoramic view) of six months back which showed a dislodged temporary filling on the lower left second premolar. The woman also told that she had six weeks of pregnancy. The patient also stated that she had pain and sensitivity on the same tooth at about one year back and went to a local dental surgeon. The dental surgeon at that time put a filling on that tooth. For three days, she could not sleep at night due to pain in that region.